Endocrine Toxicity of Micro- and Nanoplastics, and Advances in Detection Techniques for Human Tissues: A Comprehensive Review - Sabrina Bossio; Silvestro Antonio Ruffolo; Danilo Lofaro; Anna Perri; Mauro Francesco La Russa (Endocrines)
Background: Plastic pollution driven by human activities has become a critical global issue for human health. A growing literature demonstrates that micro- and nanoplastics (MNPs) contain endocrine-disrupting chemicals (EDCs) and other harmful compounds that enter the body easily, acting as agonists or antagonists for a wide range of hormonal receptors, and promoting endocrine toxicity. Endocrine disruption induced by MNPs occurs through the aberrant activation/inhibition of different signaling pathways that in addition to directly interfering with hormonal balances, trigger apoptosis, oxidative stress, and inflammation in endocrine cells. However, to date, the molecular mechanisms of these contaminants remain not completely elucidated. Furthermore, given the unanimous consensus on the negative impact of MNPs on human health, several methodologies have been developed to detect MNPs and contaminants not only in the environment but also in biological fluids and human tissues. Results: This review comprehensively summarizes the emerging experimental and clinical evidence explaining the mechanisms underlying the toxicity related to chronic plastic pollution in relation to the endocrine system. In addition, the review illustrates the new methodological approaches to detect MNPs in human biological samples, highlighting that employing complementary methods enables the precise characterization and quantification of MNPs. Conclusions: Future studies employing experimental, epidemiological, epigenetic, and multi-omics approaches are essential for understanding the short and long-term effects of MNPs on endocrine glands and developing effective strategies to mitigate their impact on human health.